2018
DOI: 10.1126/scisignal.aam8104
|View full text |Cite
|
Sign up to set email alerts
|

Guanabenz inhibits TLR9 signaling through a pathway that is independent of eIF2α dephosphorylation by the GADD34/PP1c complex

Abstract: Endoplasmic reticulum (ER) stress triggers or amplifies inflammatory signals and cytokine production in immune cells. Upon the resolution of ER stress, the inducible phosphatase 1 cofactor GADD34 promotes the dephosphorylation of the initiation factor eIF2α, thereby enabling protein translation to resume. Several aminoguanidine compounds, such as guanabenz, perturb the eIF2α phosphorylation-dephosphorylation cycle and protect different cell or tissue types from protein misfolding and degeneration. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Furthermore, quinazoline derivative called CPG-52364 is a specific inhibitor of TLR7, TLR8, and TLR9 that has shown efficacy in SLE and other cancers [464]. Most recently, an aminoguanidine compound called guanabenz (2,6-dichlorobenzylidene aminoguanidine acetate) that is used as an antihypertensive drug is shown to prevent the activation of TLR9 upon stimulation with CpG ODNs or DNA immunoglobulin complexes in endosomes [465]. The drug inhibited TLR9 activation in both murine and human DCs and B cells in vitro [465].…”
Section: Current and Future Tlr Based Therapeuticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, quinazoline derivative called CPG-52364 is a specific inhibitor of TLR7, TLR8, and TLR9 that has shown efficacy in SLE and other cancers [464]. Most recently, an aminoguanidine compound called guanabenz (2,6-dichlorobenzylidene aminoguanidine acetate) that is used as an antihypertensive drug is shown to prevent the activation of TLR9 upon stimulation with CpG ODNs or DNA immunoglobulin complexes in endosomes [465]. The drug inhibited TLR9 activation in both murine and human DCs and B cells in vitro [465].…”
Section: Current and Future Tlr Based Therapeuticsmentioning
confidence: 99%
“…Most recently, an aminoguanidine compound called guanabenz (2,6-dichlorobenzylidene aminoguanidine acetate) that is used as an antihypertensive drug is shown to prevent the activation of TLR9 upon stimulation with CpG ODNs or DNA immunoglobulin complexes in endosomes [465]. The drug inhibited TLR9 activation in both murine and human DCs and B cells in vitro [465]. Under in vivo conditions, guanabenz showed protection against CpG ODN induced systemic cytokine shock and a chemically induced autoimmune disease called SLE in mice [465].…”
Section: Current and Future Tlr Based Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the lack of ATF4 synthesis and the resistance of active DCs to mount an acute ISR, we investigated their capacity to produce pro-inflammatory cytokines and type-I IFN in a perturbed eIF2a-phosphorylation context. Importantly, we have previously shown that GADD34deficient GM-CSF BM-derived and spleen DCs, have a reduced capacity to produce different cytokines, like IFN-β (Clavarino et al, 2012b, Perego et al, 2018, further suggesting that GADD34 activity and potentially eIF2a dephosphorylation is an important process for TLR signaling and cytokine production in DCs, although contrasting with the data obtained in macrophages (Abdel-Nour et al, 2019). LPS and the dsRNA synthetic mimic polyriboinosinic:polyribocytidylic acid (poly(I:C)), that is recognized by TRIFdependent TLR3 and the MAVS-dependent cytosolic RNA helicases RIG-I and MDA5 (RLRs) Kagan, 2020, Ablasser andHur, 2020) were used to stimulate DCs (Fig.…”
Section: Importance Of the Isr For Innate Receptors Signaling In Dcsmentioning
confidence: 99%
“…CHOP facilitates apoptosis via transcription of various pro-apoptotic genes like, growth arrest and DNA-damage inducible protein (GADD34), and ER oxidoreductase 1 alpha (ERO1α) (amongst others) (Brush et al, 2003;Fransson et al, 2014;Hollander et al, 2003;Kojima et al, 2003;Novoa et al, 2001). For instance, GADD34 directs protein phosphatase 1 (PP1) to de-phosphorylate the eIF2α protein thereby causing recommencement of (Cap-dependent) protein synthesis (Choy et al, 2015;Perego et al, 2018;Rojas et al, 2015). This resumption of protein synthesis overwhelms the protein-folding capacity of the ER, which is already dealing with proteotoxicity, thereby amplifying ER stress and pushing the cell toward cell death (Han et al, 2013;Haynes et al, 2004;Malhotra and Kaufman, 2011;Sano and Reed, 2013;Sovolyova et al, 2014;Thomas et al, 2013).…”
Section: Er Stress and Inflammation: An Introduction 31 Er Stress-asmentioning
confidence: 99%